A Compound Composite Odontoma Associated with Unerupted Permanent Incisor: A Case Report - Das, Usha Mohan (Jaypee Brothers Medical Publishers, 2009)
Odontomas are the most common type of odontogenic tumors and are generally asymptomatic. Frequently they interfere with the eruption of the teeth. This is the case report of a compound composite odontoma in an 11 years old girl, which resulted in failure of eruption of the permanent maxillary right central incisor while the contralateral tooth had erupted. A calcified mass was seen in the radiograph and was provisionally diagnosed as odontoma following which the odontoma was enucleated. Routine follow-up was done for 1½ years and no recurrence was seen.